Analysis of Wastewater Reveals the Spread of Diverse Extended-Spectrum β-Lactamase-Producing E. coli Strains in uMgungundlovu District, South Africa - Siyabonga N. Gumede; Akebe L. K. Abia; Daniel G. Amoako; Sabiha Y. Essack (MDPI AG, 2021)
Wastewater treatment plants (WWTPs) are major reservoirs of antibiotic-resistant bacteria (ARB), favouring antibiotic resistance genes (ARGs) interchange among bacteria and they can provide valuable information on ARB circulating in a community. This study characterised extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli from the influent and effluent of four WWTPs in uMgungundlovu District, KwaZulu-Natal, South Africa. E. coli was enumerated using the membrane filtration method and confirmed using the API 20E test and real-time polymerase chain reaction. ESBL-producers were phenotypically identified by their susceptibility to the third-generation cephalosporins using the disc diffusion and the double-disc synergy methods against cefotaxime (30 µg) with and without 10 µg clavulanic acid. Genotypic verification was by PCR of the TEM, SHV, and CTX-M genes. The clonality of isolates was assessed by ERIC-PCR. The highest E. coli count ranged between 1.1 × 105 (influent) and 4.3 × 103 CFU/mL (effluent). Eighty pure isolates were randomly selected, ten from the influent and effluent of each of the four WWTP. ESBLs were phenotypically confirmed in 49% (n = 39) of the isolates, of which 77% (n = 30) were genotypically confirmed. Seventy-three percent of the total isolates were multidrug-resistant (MDR). Only two isolates were susceptible to all antibiotics. Overall, resistance to first and second-generation cephalosporins was higher than to third and fourth generation cephalosporins. Also, 15% of the isolates were resistant to carbapenems. The CTX-M-type ESBL (67%; n = 20) was the most common ESBL antibiotic resistance gene (ARG) followed by TEM (57%; n = 17) and SHV-types (27%; n = 8). Also, a substantial number of isolates simultaneously carried all three ESBL genes. ERIC-PCR revealed a high diversity of isolates. The diversity of the isolates observed in the influent samples suggest the potential circulation of different ESBL-producing strains within the studied district, requiring a more comprehensive epidemiological study to prevent the spread of ESBL-producing bacteria within impoverished communities.